2
$\begingroup$

During a proof of quasi-left continuity of Lévy processes, there is the next step:

$$E(f(X_{T})g(X_{T}))=E(f(X_{T^{-}})g(X_{T}))$$ for all $f,g\in C_{0},$ where $C_{0}$ is the set of all continuous functions vanishing at infinity and $T$ is stopping time.

Because of the above we conclude that $X_{T}=X_{T^{-}}$ a.s.

I was thinking in the following:

For the equality between expectation above, we have $$f(X_{T})g(X_{T})=f(X_{T^{-}})g(X_{T}) \quad \text{a.s.}$$ Then $$f(X_{T})=f(X_{T^{-}}) \quad \text{a.s.}$$ The above holds for every $f\in C_{0},$ so $X_{T}=X_{T^{-}}$ a.s. but I have doubt in this argument. I don't think this is immediatly true, isn't it?

How could be conclude this correctly?

Any kind of help is thanked in advanced.

$\endgroup$
1
$\begingroup$

Note that $$\mathbb{E}Y = \mathbb{E}Z$$ does not imply $Y=Z$ almost surely, and therefore the very first step of your reasoning doesn't work.

The idea is, essentially, to show that

$$\mathbb{E}(f(X_{T}) g(X_T)) = \mathbb{E}(f(X_{T-}) g(X_T)) \tag{1}$$

implies that the random vectors $U:=(X_T,X_T)$ and $V:= (X_{T-},X_T)$ have the same distribution. Once we know this, we can conclude that $X_T-X_T$ and $X_T-X_{T-}$ have the same distribution, and so $X_T-X_{T-}=0$ in distribution. This, however, already implies $X_T-X_{T-}=0$ almost surely.

There are several ways to prove that $U$ and $V$ have the same distribution; one possibility is to use a monotone class (or approximation) argument to show that $(1)$ implies

$$\mathbb{E}(h(X_T,X_T)) = \mathbb{E}(h(X_{T-},X_T))$$

for a suitable large class of functions $h$. Alternatively, we can observe that $(1)$ holds for bounded continuous functions $f,g$ (this follows from a simple truncation argument), and so, in particular,

$$\mathbb{E}\exp \big( i \xi X_T+ i \eta X_T \big)=\mathbb{E}\exp \big( i \xi X_{T-}+ i \eta X_T \big)$$

for any $\xi,\eta \in \mathbb{R}$. This means that $U$ and $V$ have the same characteristic function, and so $U=V$ in distribution.

$\endgroup$
  • $\begingroup$ Many thanks @saz. You're answer has been very useful. I have a doubt. I remember for measure theory, that $E(X)=0$ implies $X=0 a.s.$ So, why this kind of argument doesn't work in my idea? It's because they have different probability measure or distribution? $\endgroup$ – Squird37 Apr 4 '18 at 16:58
  • $\begingroup$ Another doubt. Why $X_{T}-X_{T^{-}}=0$ in distribution must imply that $X_{T}-X_{T^{-}}=0$ a.s? $\endgroup$ – Squird37 Apr 4 '18 at 17:01
  • $\begingroup$ @Squird37 If $X$ is a non-negative random-variable, then $\mathbb{E}(X)=0$ implies $X=0$ almost surely; without the assumption of non-negativity of $X$ the assertion fails, in general, to hold (just consider for instance a random variable $X$ such that $\mathbb{P}(X=1) = \mathbb{P}(X=-1) = 1/2$). Regarding your 2nd question: Since $X_T-X_{T-}=0$ in distribution, we know that the cdf $$F(x) := \mathbb{P}(X_T-X_{T-} \leq x)$$ satisfies $$F(x) = \begin{cases} 0, & x <0, \\ 1, & x \leq 0 \end{cases}$$ and so $$\mathbb{P}(X_{T}-X_{T-}=0) = F(0)-F(0-)=1.$$ $\endgroup$ – saz Apr 4 '18 at 17:10
  • $\begingroup$ You're totally right @saz. Many thanks for the help! $\endgroup$ – Squird37 Apr 4 '18 at 19:34
  • 1
    $\begingroup$ @Squird37 You are welcome. If you find the answer helpful, you can upvote it by clicking on the up arrow next to it. $\endgroup$ – saz Apr 4 '18 at 19:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.